The Chernobyl Herbarium: Fragments of an Exploded Consciousness - Marder, Michael (Critical Climate Change, 2016)
We entrust readers with thirty fragments of reflections, meditations, recollections, and images - one for each year that has passed since the explosion that rocked and destroyed a part of the Chernobyl nuclear power station in April 1986. The aesthetic visions, thoughts, and experiences that have made their way into this book hover in a grey region between the singular and self-enclosed, on the one hand, and the generally applicable and universal, on the other. Through words and images, we wish to contribute our humble share to a collaborative grappling with the event of Chernobyl. Unthinkable and unrepresentable as it is, we insist on the need to reflect upon, signify, and symbolize it, taking stock of the consciousness it fragmented and, perhaps, cultivating another, more environmentally attuned way of living.